Reproduction behaviors : permanencies and changes : for a contextual and dynamic approach of the fertility - (:unkn) unknown (My University, 2015)
Current levels of African fertility are, for most observers, the expression of a continuation of traditional values of ancestral essence. For those observers, the traditional values continue to determine reproductive behavior, despite the economic, political and social changes. Based on the case of the Republic of Congo, dynamic and contextual analysis of these behaviors, reveal that these are rather clear break from the current level of fertility; they suggest significant unmet need for birth control. It is possible that a Malthusian reflex develops gradually, which does not exclude the need for children, contrary to some theories. These behaviors are characterized by profound changes resulting in a disconnection between sexuality, marriage and reproduction; rejuvenation of the ages at first intercourse and first birth; postponing the age of entry into marital union and the decline of polygamy. Current reproductive behavior are likely to make fertility declining, if they were well supported institutionally in the current context. The growing importance of adolescent fertility calls for redefining the foundations of African fertility. In a context marked also by significant disruptions in the mechanisms of transmission of traditional values, enhanced by education and urbanization, it is desirable to restructure the communication on the choice of fertility control. Otherwise, the fertility transition, which is irreversible, will be at its own pace, not just at the mercy of crises, but in a sustainable way by adaptation to the conditions of life and way of production in process.
Keywords: African Research